2016
DOI: 10.1007/s00280-016-2973-2
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of adjuvant S-1/cisplatin chemotherapy followed by S-1-based chemoradiotherapy for D2-resected gastric cancer

Abstract: The results of this phase II study show that intensified adjuvant treatment with S-1/cisplatin chemotherapy and S-1-based chemoradiotherapy was tolerable and effective in reducing disease recurrence. The addition of radiotherapy to chemotherapy may be effective in D2-resected gastric cancer. Although the data here are promising, a randomized trial is needed between patients treated with the current regimen and an appropriate comparator arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…However, the patients in the phase II portion of our study had more PLNs than those in this Korean study (median, 11.5 vs 8). Recently, another Korean phase II trial evaluating adjuvant S-1/cisplatin chemotherapy with concurrent S-1/radiotherapy in gastric cancer patients after D2 LND (63.1% of patients had stage III or IV (M0) disease, with a median number of PLNs of 5.5) reported 3-year DFS and OS rates of 65.2% and 76.1%, which are similar to our results (Shim et al , 2016).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, the patients in the phase II portion of our study had more PLNs than those in this Korean study (median, 11.5 vs 8). Recently, another Korean phase II trial evaluating adjuvant S-1/cisplatin chemotherapy with concurrent S-1/radiotherapy in gastric cancer patients after D2 LND (63.1% of patients had stage III or IV (M0) disease, with a median number of PLNs of 5.5) reported 3-year DFS and OS rates of 65.2% and 76.1%, which are similar to our results (Shim et al , 2016).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the most common grade 3/4 haematological and gastrointestinal toxicities were leukopenia (11.5%) and nausea (9.6%), which were relatively less frequent than those in the aforementioned studies (Kim et al , 2012; Lee et al , 2012; Park et al , 2015; Shim et al , 2016). The exclusion of the remnant stomach from the radiation field and the application of IMRT may lead to a relatively lower rate of severe haematological (leukopenia/neutropenia) and gastrointestinal (nausea/vomiting) toxicities.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Gastric cancer (GC) is a common and lethal cancer over the world [ 1 ], with marked morbidity and mortality in China [ 2 ]. In spite of some developments in the treatment of GC, the overall survival of GC patients remains poor because most GC patients have local and distant metastases at diagnosis [ 3 5 ]. Thus, it is of vital importance to investigate the molecular mechanisms underlying metastasis to provide novel biomarkers for treatment of GC.…”
Section: Introductionmentioning
confidence: 99%
“…The ARTIST II trial is a phase III randomized trial of adjuvant chemotherapy with compound tegafur–oteracil potassium capsules (S-1) versus S-1/oxaliplatin ± RT for surgical patients with positive nodes [ 31 ]. Remarkably, the results of the phase II clinical trial based on S-1 and cisplatin showed that the postoperative concurrent CRT group improved 3 years of DFS relative to the postoperative chemotherapy group, and the toxicities were acceptable [ 32 ]. In recent years, several meta-analyses have demonstrated the role of perioperative RT in treating gastric cancer [ 33 35 ].…”
Section: Postoperative Rtmentioning
confidence: 99%